The prognostic value of PCNA expression in patients with osteosarcoma: A meta-analysis of 16 studies. Issue 41 (October 2017) - Wang, Xing; Wang, Dong; Yuan, Na; Liu, Fanxiao; Wang, Fu; Wang, Bomin; Zhou, Dongsheng
Abstract: Background: Numerous studies have attempted to determine the prognostic role of proliferating cell nuclear antigen (PCNA) expression in patients with osteosarcoma with no consistent conclusion. We performed this meta-analysis to systematically elucidate the association in a more precise manner. The purpose of this meta-analysis is to determine the prognostic role of PCNA in patients with osteosarcoma. Methods: A systematic search of relevant studies was performed in 6 electronic databases including PubMed, Embase, Web of Science, Wanfang database, China National Knowledge Internet (CNKI) database, and Chinese Biological Medical (CBM) Database (up to March 1, 2016) with the following keywords: (PCNA OR proliferating cell nuclear antigen) AND (osteosarcoma OR osteogenic tumor). A manual search of references on relevant articles was also conducted by 2 investigators independently. We performed a comprehensive evaluation of the correlation between PCNA expression and overall survival (OS) or disease-free survival (DFS) by calculating relative ratios (RR) and their corresponding 95% confidence intervals (CI) using STATA software. A fixed- or random-effect model was chosen based on the between-study heterogeneity. Results: In total, 16 studies with 691 osteosarcoma patients were included in this meta-analysis. PCNA overexpression was found in approximately 57.31% of the patients with osteosarcoma. The meta-analysis suggested that PCNA overexpression in osteosarcoma patients is associated with low OS, but not significantly with DFS (RR = 1.82, 95% CI 1.53–2.18, P  = .000; RR = 1.15, 95% CI 0.91–1.44, P  = 0.234). Sensitivity analysis for OS and DFS showed no significant difference and the pooled RRs were stable when the included studies were removed one by one. Similar results were also obtained for subgroup analysis based on different follow-ups and cutoffs to determine PCNA expression. Conclusion: The findings from this meta-analysis indicate that PCNA overexpression is an effective biomarker for poor prognosis in patients with osteosarcoma for OS. Hence, more large-scale studies are still needed to further warrant this conclusion.